2021
DOI: 10.25105/psia.v2i1.8953
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Kuat Cahaya Ruang Kelas-Studio Dengan Sni 6197:2011

Abstract: Sistem pencahayaan alami dalam ruangan ditentukan oleh kegiatan dan fungsi ruangan tersebut. Agar kenyamanan visual di dalam ruangan optimal maka kuat cahaya dalam ruangan tersebut harus sesuai dengan persyaratan. Penelitian ini bertujuan untuk mengetahui kuat cahaya alami di dalam ruangan kelas yang sekaligus berfungsi sebagai studio perancangan arsitektur, kemudian dibandingkan dengan standar kuat cahaya menurut SNI 6197:2011. Obyek penelitian adalah ruang kelas-studio arsitektur di lantai 6 Gedung C Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In previous research, referring to SNI 6197:2011, it was recommended to apply an artificial lighting pattern using dimmers on the 6th floor of Building C so that lighting conditions comply with the requirements. (Budiarti et al, 2020). Based on measurements of PMV thermal comfort in relation to the orientation and height of building C, it was found that the average thermal sensation was in the warm-hot range, but PMV index values in the west and south were neutral-slightly warm (Putri Alfiah et al, 2021).…”
Section: Differencesmentioning
confidence: 99%
“…In previous research, referring to SNI 6197:2011, it was recommended to apply an artificial lighting pattern using dimmers on the 6th floor of Building C so that lighting conditions comply with the requirements. (Budiarti et al, 2020). Based on measurements of PMV thermal comfort in relation to the orientation and height of building C, it was found that the average thermal sensation was in the warm-hot range, but PMV index values in the west and south were neutral-slightly warm (Putri Alfiah et al, 2021).…”
Section: Differencesmentioning
confidence: 99%